Recurrent stent thrombosis in a patient with acute coronary syndrome and ischemic colitis: between life-threatening thrombosis and life-threatening bleeding. (17th August 2020) - Morici, Nuccia; Cantoni, Silvia; Soriano, Francesco; Sacco, Alice; Viola, Giovanna; Esposito, Giuseppe; Oreglia, Jacopo A.; Cattaneo, Marco; Savonitto, Stefano
Abstract: Complete blood count should always be considered to tailor diagnosis and appropriate management in patients with acute ischemic heart disease. We present a challenging case of recurrent acute coronary syndrome, in the context of very high thrombotic risk due to concomitant inflammatory disease. Although no general guidelines exist for the switch between antiplatelet agents, particularly in the acute setting, in specific cases, the availability of different orally- and i.v.-acting agents and platelet function tests may allow to discriminate among multiple possible mechanisms of drug failure or side effects in the individual patient.